2022
DOI: 10.3390/jcm11144246
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Mucosal Permeability as a Surrogate Measure of Cure in Eosinophilic Esophagitis

Abstract: This study aimed to evaluate the relationship of esophageal epithelial permeability with mast cell infiltration and IgG4 deposits as well as chemokine levels in eosinophilic esophagitis (EoE) patients before and after treatment. Biopsies from controls and EoE patients before and after treatment were analyzed. Hematoxylin and eosin staining was used to show eosinophil infiltration. Paracellular permeability of the esophageal epithelium was assessed using surface biotinylation. Immunohistochemical staining was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“… 7 , 26 , 27 Levels of FLG mRNA were decreased in EoE patients, consistent with previous studies. 6 , 19 However, even without histologic remission, levels of FLG mRNA were upregulated in EoE patients after treatments, indicating that the genes related to barrier function tend to recover first.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 7 , 26 , 27 Levels of FLG mRNA were decreased in EoE patients, consistent with previous studies. 6 , 19 However, even without histologic remission, levels of FLG mRNA were upregulated in EoE patients after treatments, indicating that the genes related to barrier function tend to recover first.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, mast cells were increased in esophageal epithelium of EoE patients, consistent to previous studies. 9 , 19 , 28 Mast cells that infiltrate into the esophageal epithelia release mediators involved in the remodeling of those layers. 20 , 29 Previous studies have found that mast cell counts could be used as a marker of EoE activity in addition to eosinophil count.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Treatment responses have not been clearly defined, and normalizing mucosal eosinophil counts alone is not sufficient to achieve treatment goals 12 . However, the normalization of the esophageal mucosal barrier might signal treatment success and the cure of EoE 13 . Moreover, the rates of recurrence without treatment and the remission of EoE are still unclear.…”
mentioning
confidence: 99%